Preparation of hydrogel from propolis extract / Siti Sarah Mohd Salleh - Mohd Salleh, Siti Sarah (2023)
The proposed study goal was to develop and design a hydrogel by adding different concentrations of propolis extract (5ml, 10ml, and 15ml) manufactured via solvent casting method. The best hydrogel membrane was attempted utilising a variety of techniques including tensile strength, porosity, and gel fraction from the following concentrations. The produced hydrogel membrane was discovered to be potentially appealing as scaffolds for wound dressing applications. The best hydrogel propolis outcome was reached as 5ml of concentration propolis.